TINGKAT KEPUASAAN PETANI DALAM KEGIATAN PENYULUHAN PERTANIAN DI KECAMATAN BATURETNO KABUPATEN WONOGIRI: TINGKAT KEPUASAAN PETANI DALAM KEGIATAN PENYULUHAN PERTANIAN DI KECAMATAN BATURETNO KABUPATEN WONOGIRI - Setyo Rahyunanto; Bimoseno Sepfrian (Journal Science Innovation and Technology (SINTECH), 2026)
Agricultural extension activities are conducted by extension officers on both an individual and group basis, depending on the target audience. This study aims to assess farmer satisfaction with agricultural extension activities in Baturetno District, Wonogiri Regency. The research location was purposively selected as it is a hub for food crops, plantation crops, and horticulture, comprising 13 villages, 13 farmer group associations (gapoktan), and 111 farmer groups, yet served by a limited number of extension officers (three). A simple random sampling method was employed, resulting in a sample of 218 farmers. Data analysis was conducted using a value scale analysis. The results indicate that 69.55% of farmers fell into the "satisfied" category regarding individual extension activities, while 75.03% fell into the "satisfied" category regarding group extension activities. Overall, farmers expressed satisfaction with the agricultural extension activities—both individual and group-based—conducted by the extension officers.